Effect of parasite load on developmental mode polymorphism in Pygospio elegans : a preliminary test - Su, Houyi (2018)
In parasite-host interactions, hosts can respond to parasites by alteration of life history traits. Intraspecific larval developmental polymorphism in some polychaetes, termed poecilogony, might be a plastic response to parasite load. Poecilogony in the worm Pygospio elegans is linked to nutritional provisioning by the mother worms, while parasites can compete for nutrition. In this project, I attempted to test whether parasite load could have an effect on larval developmental mode in P. elegans. The hypothesis was that more planktonic larvae could be produced by P. elegans as a potential means of avoiding local parasites when P. elegans faced high parasite load. I developed and carried out a ddPCR assay to quantify an apicomplexan parasite, Selenidium sp., known to infect P. elegans. Then I compared parasite load between two groups of worm populations – one group featuring planktonic larvae and the other group featuring benthic larvae. Besides, I studied the correlation between genetic diversity and parasite load, and compared parasite load between populations from the Baltic Sea and the North Sea. No significant difference of parasite load was found between populations where planktonic larvae dominated and populations where benthic larvae dominated. Parasite load did not appear to have a significant effect on poecilogony. Yet lower genetic diversity significantly led to higher parasite load in the worm populations. Moreover, difference of parasite load between the Baltic Sea and the North Sea was significant, indicating that geography, which did not appear to play a direct role in larval developmental mode, might be correlated with the distribution of the apicomplexan parasite. Although extensive further research are required, this novel study on the relationship between parasite load and larval developmental mode as well as successful implementation of ddPCR for parasite load quantification will shed light on further research.